Implementation Of Student Character Formation Through PAI Learning At Bustanul Ulum Islamic Vocational School, Jember Year 2018/2019 - Moch. Afif Anshori (Cita konsultindo, 2023)
Character education is a process of transforming life values ​​to be developed in the personality of a person or student so that they become one in the behavior of that person's life. Character education is not just teaching what is right and what is wrong, more than that character education instills good habits so that students understand what is right and what is wrong, and are able to feel good grades so that students will be able to thing to do that good thing. This research focuses on how to plant, implementation and evaluationformation of student character through PAI learning at Bustanul Ulum Islamic Vocational School in 2019/2020. This type of research method is descriptive qualitative research, where research is descriptive (describes) and uses analysis, with data collection methods through observation (observation), interviews and documentation which are then analyzed by reducing irrelevant data, presenting data and drawing conclusions. The research results show that 1) Planning for instilling student character through PAI learning at the Islamic Vocational School of Bustanul Ulum has been seen optimally supported by the RKS (School Work Plan), RKAS (School Budget Activity Plan) and the 2013 Curriculum which consists of syllabus and lesson plans adapted to the conditions of students. 2) The implementation of student character cultivation through PAI learning at the Bustanul Ulum Islamic Vocational School went very well. This can be proven by the activities in the teaching and learning process which are in accordance with what is planned in the teaching and learning process which are in accordance with what is planned in the RKS, Syllabus and RPP. and pray. 3) Evaluation of students' character building through PAI learning at the Bustanul Ulum Islamic Vocational School, namely the assessment of test results, test results, exam results, which are summarized in learning completeness, the results of parental assessment activities of children when at home, then the results of children's behavior activities while at school , then at the end it will be accumulated on the value of the report card.Character education is a process of transforming life values ​​to be developed in the personality of a person or student so that they become one in the behavior of that person's life. Character education is not just teaching what is right and what is wrong, more than that character education instills good habits so that students understand what is right and what is wrong, and are able to feel good grades so that students will be able tothing to do that good thing. This research focuses on how to plant, implementation and evaluationformation of student character through PAI learning at Bustanul Ulum Islamic Vocational School in 2019/2020. This type of research method is descriptive qualitative research, where research is descriptive (describes) and uses analysis, with data collection methods through observation (observation), interviews and documentation which are then analyzed by reducing irrelevant data, presenting data and drawing conclusions. The research results show that1) Planning for instilling student character through PAI learning at the Islamic Vocational School of Bustanul Ulum has been seen optimally supported by the RKS (School Work Plan), RKAS (School Budget Activity Plan) and the 2013 Curriculum which consists of syllabus and lesson plans adapted to the conditions of students. 2) The implementation of student character cultivation through PAI learning at the Bustanul Ulum Islamic Vocational School went very well. This can be proven by the activities in the teaching and learning process which are in accordance with what is planned in the teaching and learning process which are in accordance with what is planned in the RKS, Syllabus and RPP. and pray. 3) Evaluation of students' character building through PAI learning at the Bustanul Ulum Islamic Vocational School, namely the assessment of test results, test results, exam results, which are summarized in learning completeness, the results of parental assessment activities of children when at home, then the results of children's behavior activities while at school , then at the end it will be accumulated on the value of the report card.